To Swell or Not to Swell—Design of Underground Structures in the Presence of Swelling Clays - NAT2024 - Daniel Maine (Society for Mining, Metallurgy & Exploration, 2024)
Swelling clay soils have been problematic to many types of infrastructure in the United States. However, their impact on underground construction is often misunderstood. The use of swell pressures in design of initial tunnel and shaft support lacks proper guidance and is often mis-interpreted. This paper provides insight and guidance on how to implement a geotechnical investigation program to determine if swelling soil exists at a site and how it impacts the design of temporary support systems for underground projects. An example is provided for how swell pressures were incorporated into the design of an initial support system for a rib and lagging tunnel system and problems that occurred.